Faktor-faktor yang berhubungan dengan perilaku Pemberian ASI Eksklusif di Wilayah Puskesmas Neglasari Kota Tangerang - Kamila, Nabila Humaida; Yustiyani (Journal of Religion and Public Health, 2025)
Newborn are susceptible to illness and malnutrition, making proper infant feeding feeding practice crucial,, particularly the exclusive breastfeeding. According to the Precede-Proceed theory, health related behavior, including breastfeeding, are influenced by predisposing, reinforcing, and enabling factors. This study aimed to examine the relationship between these factors with the exclusive breastfeeding practice among mothers attending the Neglasari Public Health Center, Tangerang City. This study was conducted in July-October 2023 in the Neglasari Public Health Center area. A cross-sectional study design with accidental sampling technique was employed. Data was collected through interview on 105 breastfeeding mothers who had toddlers aged 7-24 months. The association between the breastfeeding practice and independent variables were assessed using chi-square test. Findings revealed that 35.2% of the respondents provided exclusive breastfeeding. Significant association were found between the exclusive breastfeeding practice and maternal knowledge (p-value = 0.008), occupation (p-value = 0.021), age (p-value = 0.044), and parity (p value = 0.004). These results suggest that educational and support interventions tailored to mothers’ age, employment status, knowledge level, and parity could enhance exclusive breastfeeding practices.   Keywords: Maternal age, Exclusive Breastfeeding, Knowledge, Occupation, Parity